Thromboresistance of functionalized poly(methylmethacrylate): The effect of surface polarity - Kapusetti G.; Monika; Kumar Ray A.; Misra N. (My University, 2025)
An implant material when comes in contact with blood fluids (e.g., blood and lymph), adsorb proteins spontaneously on its surface. Notably, blood coagulation is influenced by many factors, including mainly chemical structure and polarity (charge) of the material. The present study describes the methodology to improve the blood compatibility of poly(methylmethacrylate) (PMMA) by incorporating ionic groups with varying polarities. PMMA has been functionalized with different groups containing positive, negative and neutral polarity by the free radical polymerization technique and suchmodification were further confirmed through Fourier transform infrared (FTIR) spectroscopy. The level of thrombogenicity was found three times lower with negatively charged PMMA in compar- ison to those of positively charged and neutral PMMA. Platelet adhesion was noted almost negligible in all samples after 10 s of blood exposure. High adsorption of fibrinogen from the blood was noticed in the test sample containing a group with positive polarity (thiouronium chloride) while there was no platelet adhesion observed even after 120 s of blood exposure in the test samples containing negatively charged (sulphate) and neutral (hydroxyl group) functional groups. © Indian Academy of Sciences.